Geodesics of Black Holes in Bumblebee Gravity Theory - Karyal, Hüseyin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
In this thesis, our main purpose is to study the geodesics of bumblebee black hole (BBH) in 4-dimension (4D), which is an exact solutions to the bumblebee gravity theory. The motions of photon and massive particles are going to be studied via the standart Lagrangian method in asymptotically flat geometry. Due to the physical constraints, instead of spacelike geodesics, we concantrate on null and timelike solutions. After finding the Euler Lagrange equations, next step is invastigating radial motions of geodesics. Moreover, exact analytical solutions are also planned to be studied for the radial and angular geodesic equations. According to our purpose, we use some numerical simulations in order to plot graphs for visualizing the geodesics. We also investigate the limit of Lorentz symmetry breaking term (LSB) by using classicsal tests which are the advance of the perihelion and bending of light. Keywords: General Relativity, Standart Model Extensions, Bumblebee Gravity Theory, Black Hole, Geodesics, Perihelion, Lorentz Symmetry Breaking, Deflective Angle.

ÖZ: Bu tezde, Bumblebee yerçekimi teorisi'nin kesin çözümleri olan 4 boyutlu (4D) kara deliklerin (BH) jeodeziklerini araştırıyoruz. Kütlesiz ve kütleli parçacıkların hareketleri asimptotik olarak düz geometride, standart Lagrangian yöntemi ile incelenecektir. Fiziksel kısıtlamalar nedeniyle, uzay benzeri jeodezikler yerine, ışık ve zaman benzeri jeodezikler üzerinde çalışılacaktır. Euler-Lagrange denklemlerini elde ettikten sonra, jeodeziklerin radyal hareketlerini analiz edeceğiz. Ayrıca, hem radyal hemde açısal jeodezik denklemler için kesin analitik çözümlerin de çalışılması planlanmaktadır. Aynı düşüncede, jeodeziklerin görüntülenmesini sağlayacak, birçok grafiği çizmek için bazı sayısal simülasyonlar yapacağız. Günberi ilerlemesi ve ışığın bükülmesi gibi bazı klasik testleri de araştırdık. Anahtar Kelimeler: Genel Görelilik, Standart Model Uzantıları, Bumblebee Yerçekimi Modeli, Kara Delik, Jeodezikler, Günberi, Lorentz Simetri Kırınımı, Sapma Açısı.
Master of Science in Physics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2020. Co-Supervisor: Prof. Dr. İzzet Sakallı, Supervisor: Assoc. Prof. Dr. Ali Övgün.
Keywords: Physics; Black Holes--Physics; General Relativity; Standart Model Extensions; Bumblebee Gravity Theory; Black Hole; Geodesics; Perihelion; Lorentz Symmetry Breaking; Deflective Angle